1997
DOI: 10.1161/01.atv.17.11.2825
|View full text |Cite
|
Sign up to set email alerts
|

The Arg 353 Gln Polymorphism Reduces the Level of Coagulation Factor VII

Abstract: Factor VII levels are regulated by environmental and genetic factors. Two polymorphisms, a G-to-A transversion at nucleotide 10,976 resulting in Arg353Gln and a decanucleotide insert at position -323 in the 5'-flanking region of the factor VII gene, have been associated with a 20% to 25% reduction in plasma factor VII levels. However Arg353Gln almost always segregates on alleles containing the insert in UK and Italian populations, thereby making it impossible to independently evaluate the impact of Arg353Gln o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
67
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 27 publications
6
67
0
5
Order By: Relevance
“…31 In our study, the well-known association between the rarer alleles and decreased FVII levels was observed. [17][18][19][20]32 Furthermore, we observed a positive correlation between FVII and BP as previously reported. 14 -16 Despite the high disequilibrium found between the 2 polymorphisms in several populations, data suggest that it is possible that both polymorphisms are functionally relevant: the 2 polymorphisms may be responsible for as much as one third of the variation in FVII levels.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…31 In our study, the well-known association between the rarer alleles and decreased FVII levels was observed. [17][18][19][20]32 Furthermore, we observed a positive correlation between FVII and BP as previously reported. 14 -16 Despite the high disequilibrium found between the 2 polymorphisms in several populations, data suggest that it is possible that both polymorphisms are functionally relevant: the 2 polymorphisms may be responsible for as much as one third of the variation in FVII levels.…”
Section: Discussionsupporting
confidence: 90%
“…14 -16 Despite the high disequilibrium found between the 2 polymorphisms in several populations, data suggest that it is possible that both polymorphisms are functionally relevant: the 2 polymorphisms may be responsible for as much as one third of the variation in FVII levels. 33 In vitro, the Arg353Gln amino acid substitution reduced FVII secretion, 19 possibly arising from a conformational alteration. The presence of the Ϫ323 decanucleotide insert was shown to reduce promoter activity compared with the absence of the decanucleotide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arg353Gln polymorphism, which was found in 90% of the patients in this cohort, is rather common; Hunault et al reported a prevalence of about 13.1% in a population of Polish blood donors (n=99) [181]. Its prevalence in the Swedish population is unknown.…”
Section: Discussionmentioning
confidence: 70%
“…However, a direct effect of this polymorphism on F VII antigen levels could also be proposed as a working hypothesis; recently, in transient transfection assays with F VII cDNA containing the base substitution, it has been shown that the Q allele determined a defective secretion of the molecule from the cells. 16 Beside the R353Q polymorphism, the −323 0/10 bp promoter has also been demonstrated to be functionally relevant; the rare insertion allele 10/bp, indeed, reduced the promoter activity, as compared to the common allele, in transfection experiments. 17 Therefore, it is conceivable that the promoter polymorphism, due to its functionality and strong linkage disequilibrium with the R353Q polymorphism, could also contribute to the effect of FVII genotype on the risk of MI, or even be the main determinant of the effect.…”
mentioning
confidence: 99%